Case Report: Clinical characteristics and multidisciplinary collaborative management of congenital tuberculosis in extremely preterm twins and preterm infants: a report of three cases and literature review - Yang, Liming; Yue, Lunli; Chen, Qiong; Huang, Xi (Frontiers in Pediatrics, 2026)
AimsThis study aims to report three cases of maternal-fetal transmission of tuberculosis in premature infants, systematically analyze their clinical characteristics, diagnostic processes, and treatment outcomes, explore the core role of the multidisciplinary team (MDT) in optimizing diagnosis and treatment, and provide an evidence-based basis for early identification, precise diagnosis, and effective therapy to reduce high mortality rates and enhance clinical management levels.MethodsThrough retrospective case reports combined with a literature review, three cases of maternal-fetal transmission of tuberculosis in extremely premature twins and a premature infant were reported. Integration of maternal history, placental pathology assessment (such as acid-fast staining positive bacilli and Mycobacterium tuberculosis qPCR detection), imaging examinations (such as chest x-ray and CT), etiological tests (such as NGS), and fundus examination results. Treatment adopted individualized anti-tuberculosis regimens (isoniazid 10–15 mg/kg/d, rifampicin 15–20 mg/kg/d, pyrazinamide 20–30 mg/kg/d), collaboratively developed by MDT (neonatology, infectious diseases, pharmacists, and ophthalmology experts), combined with supportive therapies (such as mechanical ventilation, blood transfusion, and nutritional support). Follow-up evaluated growth and neurodevelopmental outcomes.ResultsThis study reported three cases of maternal-fetal transmission of tuberculosis, involving extremely premature twins at 27+4 weeks (birth weights 890 g and 880 g) and one premature infant at 34+1 weeks. The twins' mother had a history of tuberculosis of the uterus or uterine TB, fever during pregnancy, and postpartum confirmed tuberculosis (positive placental pathology and NGS); infants presented with respiratory distress and fever. Diagnostic basis included maternal history, placental pathology, NGS detection of Mycobacterium, and fundus examination (retinal white spot changes). Under MDT collaboration, anti-tuberculosis treatment (isoniazid, rifampicin, pyrazinamide) and supportive therapy controlled the infection. The older twin (male) was hospitalized for 93 days, weight reached 3,670 g, and at follow-up to corrected age of 4.5 months, weight increased to 7.44 kg, length 59 cm; the younger twin (female) hospitalized for 60 days, weight 2,170 g, follow-up to corrected age of 4.5 months, weight 6.62 kg, length 54 cm. The twins had normal growth and development, no permanent visual impairment. The premature infant case was similar with good prognosis.ConclusionThe diagnosis of maternal-fetal transmission of tuberculosis in extremely premature and premature infants is highly challenging due to the lack of specific symptoms, often misdiagnosed as sepsis or respiratory distress syndrome (RDS). This study observed through three cases that integrating chest imaging, etiological tests (such as NGS), placental pathology assessment, and fundus screening (such as retinal white spot changes) aids in early diagnosis. MDT collaboration in developing individualized anti-tuberculosis treatment plans (including isoniazid, rifampicin, and pyrazinamide) supplemented with supportive therapy effectively improves infant prognosis, with normal weight gain post-discharge, good development, and no permanent visual damage. Strengthening prenatal screening and monitoring for high-risk pregnant women helps prevent such cases. In the future, multicenter studies should further optimize diagnostic criteria and treatment strategies to reduce mortality and improve neonatal quality of life.